Hardiness Dan Resiliensi Terhadap Intensi Wirausaha Pada Mahasiswa - Nursakinah Oktaviana Sasmita; Lenny Utama Afriyenti (Jurnal Kajian Ilmiah, 2023)
Several campuses organize Independent Entrepreneurship, this is done to look for potential leaders and business innovators who can reduce the unemployment rate in Indonesia, this is called intention. Intention is defined as something that exists within a person which refers to the desire to carry out certain behavior. Students who focus on pursuing entrepreneurship are faced with various challenges such as uncertainty, all kinds of risks and even failure. Developing this intention in students is what will influence the process of choosing a career as an entrepreneur. Students who run entrepreneurship tend to have a higher level of resilience. Of course, this requires high hardiness which will make individuals strong in their achievement of becoming an entrepreneur. This research took data from 118 individuals who used the internet and collected it by distributing the Entrepreneurial Intention Questionnaire (EIQ) questionnaire via social media. The data was analyzed and the results showed that there was a significant positive relationship between resilience and hardiness on entrepreneurial intentions. Every student who wants to start a new business must have an attitude of hardiness, especially strong commitment. The higher the level of hardiness, the lower the level of stress.